PENGARUH LITERASI EKONOMI DAN KELOMPOK REFERENSI TERHADAP PERILAKU KONSUMSI SISWA SMK MUHAMMADIYAH 2 PEKANBARU (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This study aims to analyze consumption behavior, which is influenced by economic literacy and reference groups, either partially or simultaneously. Population of the study was all students at Vocational High School of Muhammadiyah 2 Pekanbaru. By using proportional random sampling techniques, 205 students were gathered as respondents. Data was obtained using questionnaire and test techniques. The research variable data was analyzed descriptively and then the relationship between variables was analyzed using multiple linear regression analysis techniques with the SPSS assisted. The results of this study show that students' consumption behavior is partially influenced by economic literacy and reference groups, respectively by 0.328 and 0.522; Meanwhile, simultaneously, students' consumption behavior is equally influenced by 0.525 by these two influencing variables. At a significance level of 5%, the consumption behavior of students, SMK Muhammadiyah 2 Pekanbaru, is significantly influenced by economic literacy and reference groups.